Sujeitos políticos da economia solidária e comunitária na Bolívia: tendências e modelos do setor camponês-indígena - Isabelle Hillenkamp (Ciências Sociais Unisinos)
This article analyzes the trends and models of community and solidarity economy in the peasant-indigenous sector in Bolivia. From the recent dispute between community economic organizations (OECOMs) and peasant economic organizations (OECAs) caused by the new legislative framework, it goes back to the historical trajectories that explain the forms of collective, political and socio-economic organization in the peasant-indigenous sector. At a first level, the article argues that these two organizational models are based on different modes of governance of the commons in rural communities, focused on mere family reproduction associated with local governance through agrarian unions in the first case and the voluntary association of producers in the same sector of activity in the second case. At a second level, the article considers the constitution of OECOMs and OECAs as political subjects. It points to a State-based conception of the public sphere in the case of the agrarian unions and the OECOMs that aims at political and institutional recognition but can also lead to a loss of autonomy. The OECAs are distinct in that they have a broader vision of the collective (not determined by the unions and communitarian structures) and of the public (not limited to the State), without always being able to avoid the risk of corporatism. This analysis ultimately suggests reflection and action for the further democratization of the economy.